The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1152/ajpheart.00346.2019
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota regulates cardiac ischemic tolerance and aortic stiffness in obesity

Abstract: The gut microbiota has emerged as an important regulator of host physiology, with recent data suggesting a role in modulating cardiovascular health. The present study determined if gut microbial signatures could transfer cardiovascular risk phenotypes between lean and obese mice using cecal microbiota transplantation (CMT). Pooled cecal contents collected from obese leptin-deficient (Ob) mice or C57Bl/6j control (Con) mice were transplanted by oral gavage into cohorts of recipient Ob and Con mice maintained on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 61 publications
2
25
0
1
Order By: Relevance
“…Our result showed that relative abundances of Christensenellaceae were significantly enhanced after 6 weeks of exercise and diet intervention. In the study of obese gut flora, a variety of physiological characteristics related to obesity are affected by specific gut flora (52,53). In our study, we found that microbial changes were significantly correlated with changes in SEVR, AIx75, and resting HR.…”
Section: Discussionsupporting
confidence: 54%
“…Our result showed that relative abundances of Christensenellaceae were significantly enhanced after 6 weeks of exercise and diet intervention. In the study of obese gut flora, a variety of physiological characteristics related to obesity are affected by specific gut flora (52,53). In our study, we found that microbial changes were significantly correlated with changes in SEVR, AIx75, and resting HR.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, the microbiota in the context of obesity can influence many pathologies in different organs or tissues (Jamar, Ribeiro, and Pisani 2020). In an experimental model of cardiac ischemia, Battson et al demonstrated that gut microbiota transplantation alters cardiovascular pathology in lean and obese mice independent of dietary intake, whereas myocardial infarct size was reduced in obese mice receiving lean microbiota and worsened in lean mice receiving obese microbiota (Battson et al 2019). This suggests that "obese microbiota" can be harmful in the development of heart diseases.…”
Section: The Microbiota Gut-lung Axis and Immune Response In Obesitymentioning
confidence: 99%
“…Accumulating studies identified the roles of SCFAs and related fatty acylations in CVDs. SCFAs not only affect the progression of CVD but also regulate CVD-associated syndromes, such as obesity [64], insulin sensitivity [64,178,179], diabetes [180]. There is now ample evidence that the abovementioned eight SCFAs are protective in CVDs, except that the role of succinate seems to be destructive.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%